On guard : defending your faith with reason and precision - Craig, William Lane. (Colorado Springs, Colo. : David C. Cook, 2010)
Provides four arguments for God's existence, looks at the historicity of the resurrection of Jesus, analyzes suffering, and describes why religious relativism does not work, in a guide to help Christians defend their faith.
Foreword / Lee Strobel -- What is apologetics? -- What difference does it make if God exists? -- Why does anything at all exist? -- Personal interlude : a philosopher's journey of faith, part one -- Why did the Universe begin? -- Why is the Universe fine-tuned for life? -- Can we be good without God? -- What about suffering? -- Personal interlude : a philosopher's journey of faith, part two -- Who was Jesus? -- Did Jesus rise from the dead? -- Is Jesus the only way to God?
"Some material adapted from Reasonable Faith, third edition, by William Lane Craig, c2008."--T.p. verso
Includes bibliographical references.
Keywords: Apologetics; Faith and reason